In situ nanoparticle embedding for authentication of epoxy composites - Pansare, Amol V.; Khairkar, Shyam R.; Shedge, Amol A.; Chhatre, Shraddha Y.; Patil, Vishwanath R.; Nagarkar, Amit A. (Advanced Materials, 2018)
In situ reduction of chloroauric acid inside an amine-cured epoxy matrix leads to formation of gold nanoparticles which are embedded inside the part. This phenomenon is leveraged to design an authentication system for composites wherein the particles are embedded spatially and are invisible to the naked eye. Under UV light, the particles diffract light and create an easily visible path. The particles penetrate inside the part and create a permanent, cost-effective, tamper-proof code. The advantage of this technique is that this authentication system can be built in composite parts after fabrication of the composite structure. As very small amount (nanograms) of particles are present in the part, negligible change in the thermal characteristics of the parent matrix is observed. The particles can be embedded easily in carbon fiber as well as glass fiber reinforced epoxy structures.
Keywords: authentication; barcoding; composites; embedded nanoparticles; Epoxy

AgQDs employing black box synthetic strategy: photocatalytic and biological behavior - Pansare, Amol V.; Shedge, Amol A.; Chhatre, Shraddha Y.; Das, Debabrata; Murkute, Punam; Pansare, Shubham V.; Nagarkar, Amit A.; Patil, Vishwnath R.; Chakrabarti, S. (Journal of Luminescence, 2019)
This investigation relates FRET, photocatalytic and a biological study of AgQDs which found to be dependent on particle size and capping agent used. Surface of AgQDs was one of the most important factors that govern its activity. AgQDs with BSA binding was systematically studied by fluorescence quenching and electrostatic interaction. AgQDs mainly interacted to site II of BSA, binding distance r evaluated according to the FRET theory and was 4.6 nm for AgQDs, which suggested transfer of energy (non-radioactive) between surface modified AgQDs and biological molecule BSA. The photocatalytic activity of AgQDs for the appreciable degradation of erythrosine dye using Ultraviolet-B light was investigated. AgQDs showed specific antibacterial activity against E. coli bacterial stain. Quantum dots displayed a pronounced and specific activity causing > 50% growth of COLO-205 and MCF-7 human cancer Cells at concentrations < 10(-7 )M. Hence, present black box synthetic protocol of AgQDs could be life science application.
Keywords: AgQDs; Black box; COLO-205; Photocatalytic

Hydrophobic interpenetrating polyamide-PDMS membranes for desalination, pesticides removal and enhanced chlorine tolerance - Khairkar, Shyam R.; Pansare, V, Amol; Shedge, Amol A.; Chhatre, Shraddha Y.; Suresh, A. K.; Chakrabarti, Subhananda; Patil, Vishwanath R.; Nagarkar, Amit A. (Chemosphere, 2020)
Hydrophobic membranes for desalination and toxic organic pollutant removal have been fabricated using polyamide - PDMS (polydimethylsiloxane) chemistries in a one-step protocol. The curing of polyamide and PDMS are orthogonal and co-curing both networks imparts hydrophobicity to the thin film composite membranes. The membranes exhibit increased adsorption of pesticides from the feed water along with maintaining excellent salt rejection capability (97% NaCl rejection), thus giving the membranes a multifunctional character. Three toxic pesticides have been used in this study to demonstrate the viability of combining osmosis desalination technology with organic matter adsorption. The membranes also show excellent resistance to fouling by toxic pesticides (85% salt rejection vs 67% for commercial membranes in the presence of pesticides) and significantly improved chlorine tolerance (93.8% salt rejection vs 86.5% for commercial membranes after 20 h of exposure to sodium hypochlorite solution). (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: PDMS (Polydimethylsiloxane); Pesticide rejection; Salt rejection; Water purification membranes

Nanocomposite of functional silver metal containing curcumin biomolecule model systems: Protein BSA bioavailability - Shedge, Amol A.; Pansare, Shubham V.; Khairkar, Shyam R.; Chhatre, Shraddha Y.; Chakrabarti, S.; Nagarkar, Amit A.; Pansare, Amol V.; Patil, Vishwanath R. (Journal of Inorganic Biochemistry, 2020)
Curcumin, a constituent of Curcuma longa L-Zingiberaceae is used in traditional Indian and worldwide medicine and shows anticancer and antioxidant properties. Curcumin has numerous biological and pharmacological ac-tivities but due to its hydrophobic nature, the major drawback is poor absorption and rapid elimination, rendering curcumin with the tag of a poor biomaterial. Hence, there is a need to develop functional metal containing curcumin model systems (FMCCMS) as a metallo-biomolecule to enhance the bioavailability of curcumin. We designed the interaction of silver metal ion with curcumin to form curcumin-silver nanocomposite (CURC-AgNCP) via ultrasonic synthetic route. Formations of FMCCMS were characterized by spectroscopic techniques. The crystalline face-centered cubic pattern and particle size of the nanocomposite was evaluated using X-ray diffraction and high-resolution transmission electron microscopy. The bonding of silver metal to curcumin was confirmed by X-ray photon spectroscopy. Interaction of the nanocomposite with bovine serum albumin (BSA) protein was performed using excitation, emission, and circular dichroism spectroscopy. In binding interaction of BSA, the negative value of Delta S degrees (-358.04 J mol(-1) K-1) and Delta H degrees (-129.42 KJ mol(-1)) demonstrates the hydrophilic nature of the nanocomposite. The binding distance r evaluated according to the Forster resonance energy transfer theory and was 4.69 nm for CURC-AgNCP, which suggested non-radiative transfer of energy between CURC-AgNCP and BSA. The role of FMCCMS metallo-biomolecule CURC-AgNCP in medicine for cancer activity can have immense importance and hence we performed Sulphorhodamine B based in-vitro cytotoxicity assay on human breast cancer Michigan Cancer Foundation-7 cell line.
Keywords: Ag-based CURC biomaterials; Breast cancer; Metal in medicine; Metallobiomolecules; Nanocomposite

Biological macromolecule chitosan grafted co-polymeric composite: bio-adsorption probe on cationic dyes - Khairkar, Shyam R.; Pansare, V. Shubham; Shedge, Amol A.; Chhatre, Shraddha; Kulal, Dnyaneshwar K.; Patil, Vishwanath R.; Pansare, V. Amol (Polymer Bulletin, 2022)
Chitosan biological macromolecule is a versatile polymer; chemical modification has been carried out that lead to the formation of chitosan grafted polymers composites (Chito-g-PC). We proposed synthesis of six various Chito-g-PC as sorbents for toxic dyes. A novel graft copolymerization method based on radical polymerization with vinyl monomer like acrylic acid, acrylamide, N-isopropylacrylamide, methacrylic acid and polyacrylonitrile were utilized in order to address the large amount of swelling at four different pH buffers solution. The effect of initiator and monomer concentration, time and temperature on % grafting and % grafting efficiency were performed. Comparative characterization of Chito and Chito-g-PC were evaluated by SEM, XRD and FTIR, as well as solubility characteristics of the composites were determined by various pH buffer solution. Cationic toxic dyes Malachite green (MG) and Methylene blue (MB) were selected as the sorbet, and Chito-g-PC were used as biosorbents. Thermodynamic analysis showed that the sorption process was spontaneous and endothermic with an increased randomness. The sorption experiments were realized with six different Chito-g-PC for MG and MB at various pH.
Keywords: Acrylamide; acrylic acid; Bio sorbent; Chitosan biological macromolecule

Deciphering the sensing of alpha-amyrin acetate with hs-DNA: a multipronged biological probe - Pansare, V. Amol; Shedge, Amol A.; Sonawale, Maryappa C.; Pansare, V. Shubham; Mahakal, Akshay D.; Khairkar, Shyam R.; Chhatre, Shraddha Y.; Kulal, Dnyaneshwar K.; Patil, Vishwanath R. (RSC Advances, 2022)
In this study, we focus on the biomimetic development of small molecules and their biological sensing with DNA. The binding of herring sperm deoxyribonucleic acid (hs-DNA) with naturally occurring bioactive small molecule alpha-amyrin acetate (alpha-AA), a biomimetic - isolated from the leaves of Ficus (F.) arnottiana is investigated. Collective information from various imaging, spectroscopic and biophysical experiments provides evidence that alpha-AA is a minor groove sensor of hs-DNA and preferentially binds to the A-T-rich regions. Interactions of different concentrations of small molecule alpha-AA with hsDNA were evaluated via various analytical techniques such as UV-Vis, circular dichroism (CD) and fluorescence emission spectroscopy. Fluorescence emission spectroscopy results suggest that alpha-AA decreases the emission level of hsDNA. DNA minor groove sensor Hoechst 33258 and intercalative sensor EB, melting transition analysis (T-M) and viscosity analysis clarified that alpha-AA binds to hs-DNA via a groove site. Biophysical chemistry and molecular docking studies show that hydrophobic interactions play a major role in this binding. The present research deals with a natural product biosynthesis-linked chemical-biology interface sensor as a biological probe for alpha-AA: hs-DNA.

X-ray fluorescence-based spray-on ``elemental barcodes'' - Pansare, Amol V.; Terrasi, Giovanni P.; Pansare, Shubham V.; Khairkar, Shyam; Shedge, Amol A.; Zote, Santosh W.; Chhatre, Shraddha; Barbezat, Michael; Patil, Vishwanath R.; Nagarkar, Amit A. (Advanced Materials Technologies, 2025)
A novel spray-on elemental barcode technology is reported for the secure, permanent, and tamper-proof identification of polymeric and fiber-reinforced composite materials. This system utilizes the in situ reduction of metal salts to nanoparticles embedded within a polymer matrix, creating a unique barcode that is detectable through X-ray fluorescence (XRF). The barcode's composition is based on the metallic nanoparticle mixture and offers a semi-quantitative, non-destructive, and thermally stable method for material authentication. The process is straightforward, involving the manual application of metal salt solutions followed by mild heating, ensuring no significant alteration to the material's properties. The barcodes can be read through protective coatings or paints and are robust even under extreme conditions, such as high temperatures. This low-cost method does not introduce additional manufacturing steps and demonstrates significant potential for anti-counterfeiting and lifecycle tracking in various industries. Moreover, with an information density of up to 12 bits mm-1, this elemental barcode significantly surpasses the data storage capabilities of traditional optical barcodes. This approach holds promise for broad substrate applicability and can be expanded to other metals and reduction protocols, making it versatile for diverse material applications.
Keywords: authentication; barcoding; embedded nanoparticles; epoxy thermosets; fiber-reinforced composite; in situ reduction